Bijak Bermedia Sosial dan Konsekuensi Hukumnya bagi Remaja (Sosialisasi Hukum di SMA Negeri Pagerbarang Kabupaten Tegal) - Soesi Idayanti; Moh. Taufik; Andi Zulfa Majida; Sugiyanto Sugiyanto (Institut Nalanda, 2026)
Being wise on social media for teenagers means using digital platforms consciously, responsibly, and in accordance with legal and ethical norms. Teenagers need to understand that every post, comment, and dissemination of information has legal implications, such as the risk of privacy violations, defamation, hate speech, and the spread of hoaxes. This understanding is crucial to ensuring that social media is used positively as a means of expression, education, and social interaction without causing future legal problems. Teenagers who upload content containing insults, accusations, or negative comments about others may be subject to legal sanctions. Posts on social media are considered statements in a public space, so even if made privately or jokingly, they still have the potential to violate the law if they harm the honor of others. The legal consequences include criminal proceedings, fines, and/or imprisonment. Therefore, digital literacy education and parental guidance are essential to help teenagers develop critical thinking, self-control, and ethical awareness in navigating online environments safely and responsibly.